Revitalizing MSMEs through Innovative Financial Products in Islamic Banking - Salma Puji Rohimah (Journal of Islamic Economics and Business, 2023)
Empowerment of Small and Medium Enterprises (SMEs) and Cooperatives have a crucial role in national development based on a people's economic system, with the aim of not only reducing income disparities and employment, but also achieving economic inclusiveness and justice. Islamic banking is a financial institution that acts as an intermediary in financial matters by complying with Islamic sharia principles, collecting, managing and distributing funds to the public. This study uses a qualitative descriptive analysis method to examine the roles and products offered by Islamic banking to SMEs and cooperatives. The results of the study show that the products offered, such as murabaha, musyarakah, and people's business loans, contribute to advancing SMEs and cooperatives. In addition, Islamic financial institutions continue to innovate with various banking products and services, supporting sustainable economic growth. Thus, empowering SMEs and cooperatives through sharia banking is the main foundation in supporting national development that is just, inclusive and forward-looking to achieve sustainable development goals.